1999
DOI: 10.1111/j.1502-3931.1999.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphological study of large canids from the lower Pleistocene of southeastern Spain

Abstract: An ecomorphological analysis of the skeletal remains of large canids, Canis (Xenocyon) falconeri and Canis etruscus (Mammalia, Carnivora, Canidae), preserved in an assemblage of large mammals from the lower Pleistocene site at Venta Micena (Guadix-Baza Basin, Orce, Granada, southeastern Spain) is reported. Mean body mass of adult individuals was estimated to be around 10 kg for C. etruscus and approximately 28 kg for C. falconeri using multiple regression.A comparative study of tooth measurements in modern can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 54 publications
(55 reference statements)
5
88
1
Order By: Relevance
“…They studied the diet and morphometric indexes of some carnivorans of Patagonia and found a good correspondence in one season (spring-summer) but not in the other (fall-winter). This work showed that at fine scales (e.g., annual variation) morphology could not correctly reconstruct prey-predator relationships, but at a larger scale there is a good correlation between morphology and diet as was reported by other authors (e.g., Van Valkenburgh 1988, 1989Palmqvist et al 1999;Friscia et al 2007). …”
supporting
confidence: 57%
“…They studied the diet and morphometric indexes of some carnivorans of Patagonia and found a good correspondence in one season (spring-summer) but not in the other (fall-winter). This work showed that at fine scales (e.g., annual variation) morphology could not correctly reconstruct prey-predator relationships, but at a larger scale there is a good correlation between morphology and diet as was reported by other authors (e.g., Van Valkenburgh 1988, 1989Palmqvist et al 1999;Friscia et al 2007). …”
supporting
confidence: 57%
“…Palmqvist et al [296] attributed bilateral asymmetry and dental anomalies in a single complete skull of the large lower-Pleistocene canid Canis (Xenocyon) falconeri to possible isolation and small population size. Of 66 skeletal remains of this species, all but this one skull were fragmented and scattered; most teeth could not be assigned to particular individuals.…”
Section: Fossil Materialsmentioning
confidence: 99%
“…II). Moreover, developmental instability and fluctuating asymmetry have already been used as an explanation for dental anomalies in canids (Palmqvist et al, 1999), and in otters (Hauer, 2002). Ongoing morphometric analyses to determine the level of fluctuating asymmetry will help establish the influence of environmental stressors in this species, and consequently find support for this hypothesis.…”
Section: Discussionmentioning
confidence: 96%